Investigation of sodalite frameworks containing chalcogen-based anions - Pious Arya (2003)
Compounds with the formulae Nas[AlSiO4]6X and M2Na6[AlSiO4]6X where M = Ca2+, Mg2+ and X = SeO32-, SO42- and TeO32- have been prepared using solid state methods. Oxidation–reduction reactions under flowing oxygen, hydrogen or 90 % hydrogen–10 % hydrogen sulphide have been used to alter the nature of X by intercage reaction. Product purity was investigated by powder X-ray diffraction, vibrational spectroscopy and MASMNR. Structural determination of new phases was achieved by the Rietveld analysis of powder X-ray diffraction data. [Continues.]